Food reconstruction using isotopic transferred signals (FRUITS): a Bayesian model for diet reconstruction - Fernandes, Ricardo; Millard, Andrew R; Brabec, Marek; Nadeau, Marie-Josée; Grootes, Pieter (PloS one, 2014)
Human and animal diet reconstruction studies that rely on tissue chemical signatures aim at providing estimates on the relative intake of potential food groups. However, several sources of uncertainty need to be considered when handling data. Bayesian mixing models provide a natural platform to handle diverse sources of uncertainty while allowing the user to contribute with prior expert information. The Bayesian mixing model FRUITS (Food Reconstruction Using Isotopic Transferred Signals) was developed for use in diet reconstruction studies. FRUITS incorporates the capability to account for dietary routing, that is, the contribution of different food fractions (e.g. macronutrients) towards a dietary proxy signal measured in the consumer. FRUITS also provides relatively straightforward means for the introduction of prior information on the relative dietary contributions of food groups or food fractions. This type of prior may originate, for instance, from physiological or metabolic studies. FRUITS performance was tested using simulated data and data from a published controlled animal feeding experiment. The feeding experiment data was selected to exemplify the application of the novel capabilities incorporated into FRUITS but also to illustrate some of the aspects that need to be considered when handling data within diet reconstruction studies. FRUITS accurately predicted dietary intakes, and more precise estimates were obtained for dietary scenarios in which expert prior information was included. FRUITS represents a useful tool to achieve accurate and precise food intake estimates in diet reconstruction studies within different scientific fields (e.g. ecology, forensics, archaeology, and dietary physiology).
Keywords: Animals; Uncertainty; Models, Statistical; Nitrogen Isotopes; Animal Feed; Food Analysis; stravovací zvyklosti; Bayesova věta; lidé; statistické modely; nejistota; Bayes Theorem; dieta; analýza potravin; Diet; Feeding Behavior; izotopy dusíku; krmivo pro zvířata; zvířata; Humans